Magnetic Resonance Imaging Diagnosis of Hepatocellular Carcinoma in Cirrhotic Patients: Where Are We Now? - Miguel Ramalho; Mamdoh AlObaidy; António P. Matos; Richard C. Semelka (Acta Médica Portuguesa, 2016)
n/a